Lipopolysaccharide modifies sodium current kinetics through ROS and PKC signalling in induced pluripotent stem-derived cardiomyocytes from Brugada syndrome patient - Liao, Zhenxing; Li, Yingrui; Fan, Xuehui; Yang, Zhen; El-Battrawy, Ibrahim; Zhou, Xiao-Bo; Akın, Ibrahim (Journal of cardiovascular development and disease, 2022)
Studies have suggested a connection between inflammation and arrhythmogenesis of Brugada syndrome (BrS). However, experimental studies regarding the roles of inflammation in the arrhythmogenesis of BrS and its underlying mechanism are still lacking. This study aimed to investigate the influence of inflammation on BrS-phenotype features using human-induced stem cell-derived cardiomyocytes (hiPSC-CMs) from a BrS-patient carrying an SCN10A variant (c.3749G > A). After LPS treatment, the peak sodium current decreased significantly in SCN10A-hiPSC-CMs, but not in healthy donor-hiPSC-CMs. LPS also changed sodium channel gating kinetics, including activation, inactivation, and recovery from inactivation. NAC (N-acetyl-l-cysteine), a blocker of ROS (reactive oxygen species), failed to affect the sodium current, but prevented the LPS-induced reduction of sodium channel currents and changes in gating kinetics, suggesting a contribution of ROS to the LPS effects. Hydrogen peroxide (H2O2), a main form of ROS in cells, mimicked the LPS effects on sodium channel currents and gating kinetics, implying that ROS might mediate LPS-effects on sodium channels. The effects of H2O2 could be attenuated by a PKC blocker chelerythrine, indicating that PKC is a downstream factor of ROS. This study demonstrated that LPS can exacerbate the loss-of-function of sodium channels in BrS cells. Inflammation may play an important role in the pathogenesis of BrS.